Simulation research on carbon emissions trading based on blockchain - Zhou, Qing; Zhang, Qi (Journal of Environmental Engineering and Landscape Management, 2022)
Global warming caused by greenhouse gases is one of the problems that need to be solved urgently. Blockchain technology can achieve automatic quota certification and settlement, providing a new direction for carbon emissions trading. This paper provides a quantitative analysis of blockchain-based carbon emissions trading through the Repast simulation platform. Firstly, it designs the blockchain-based carbon emissions trading simulation framework from a macro perspective, including identity and quota certification, quota trading, risk prevention and smart contracts management. Then, it establishes a blockchain-based carbon emissions trading simulation model and formulates the behavior rules of the government, investors and company agents and market transaction processes. Finally, it simulates the carbon emissions trading based on public chain and private chain on the Repast platform, and analyzes the simulation results.